2019
DOI: 10.1007/s00464-019-07263-2
|View full text |Cite
|
Sign up to set email alerts
|

Robot assisted versus laparoscopic suturing learning curve in a simulated setting

Abstract: Background Compared to conventional laparoscopy, robot assisted surgery is expected to have most potential in difficult areas and demanding technical skills like minimally invasive suturing. This study was performed to identify the differences in the learning curves of laparoscopic versus robot assisted suturing. Method Novice participants performed three suturing tasks on the EoSim laparoscopic augmented reality simulator or the RobotiX robot assisted virtual reality simulator. Each participant performed an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 27 publications
(41 reference statements)
0
30
0
Order By: Relevance
“…Robotic surgery was currently largely employed in many surgical specialties, in particular in urologic procedures [3]. Robotic surgery offers a faster learning curve, especially regarding suture techniques [4][5][6], with the presumably shared benefits of laparoscopy including less perioperative morbidity, improved visibility and precision, and faster recovery. The disadvantages of the robotic approach include the cost of the device [7] and the fact that they are not currently available in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery was currently largely employed in many surgical specialties, in particular in urologic procedures [3]. Robotic surgery offers a faster learning curve, especially regarding suture techniques [4][5][6], with the presumably shared benefits of laparoscopy including less perioperative morbidity, improved visibility and precision, and faster recovery. The disadvantages of the robotic approach include the cost of the device [7] and the fact that they are not currently available in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations in space and movement of SPA laparoscopy lead to conflicts among instruments, thus inhibiting careful manipulation. Therefore, SPA laparoscopy usually requires a long learning curve, and skilled surgeons most often undertake the procedure (29,30). On the other hand, a relatively large umbilical hole created in SPA, compared with RAL, facilitates further extracorporeal procedures and aids in the removal of the bulky specimen.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the learning curve for RS is generally shorter than that for CL [64,65]. In particular, suturing technique is faster with a robot than in CL [66]. Of course, that might not be an important issue for experienced surgeons; however, it can be a strong advantage to beginners.…”
Section: Discussionmentioning
confidence: 99%